Land Grabbing and Home Country Development Chinese and British Land Acquisitions in Comparative Perspective - Goetz, Ariane (Edition Politik, 2019)
Since 2008, foreign land acquisitions have attracted international attention under the term »land grabbing.« Illustrated by rich and nuanced empirical accounts of forty Chinese and British investment projects in Sub-Saharan Africa, Ariane Goetz explains the phenomenon of »land grabbing« from the perspective of two investor countries. She reflects on Chinese and British public policy, state-society relations, national developmental contexts, ideologies, and international relations and thereby gives insights into the political economies that enable these investments as well as the development ambitions and institutionalized paradigms of which they form a part.